TRADISI KEINTELEKTUALAN DAN BIOGHRAFI DAN PEMIKIRAN NURCHALISH MADJID - Fakhrurrazi Fakhrurrazi (Pascasarjana UIN Sumatera Utara, 2021)
Thinking that is progressive and useful for the general public is very much needed. It is for the sole sake of progress in the community. However, the problems in society are so complex that certain groups want to change. One of the most famous figures in Islam is Nurchalish Madjid, famous for his renewal model. The thoughts of Cak Nur (Nurcholis Madjid) are identical to Islam, Indonesianness and modernity. He was the first character to express this; Saifullah said in Pena Almuslim,